2005
DOI: 10.1097/00006982-200504000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography of Choroidal Nevus in 120 Patients

Abstract: OCT is a useful diagnostic modality for imaging the retina overlying a choroidal nevus. Numerous overlying changes such as subretinal fluid, retinal edema, retinal thinning, and photoreceptor attenuation are visible by OCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 22 publications
1
53
0
6
Order By: Relevance
“…However, the overlying retina can show several alterations. In an assessment of 120 eyes with choroidal nevus using OCT, Shields et al [7] found related retinal findings that included overlying retina edema (15%), subretinal fluid (26%), retinal thinning (22%), drusen (41%), and RPE detachment (12%) (Figs. [1][2][3].…”
Section: Choroidal Tumor and Choroidal Nevusmentioning
confidence: 99%
“…However, the overlying retina can show several alterations. In an assessment of 120 eyes with choroidal nevus using OCT, Shields et al [7] found related retinal findings that included overlying retina edema (15%), subretinal fluid (26%), retinal thinning (22%), drusen (41%), and RPE detachment (12%) (Figs. [1][2][3].…”
Section: Choroidal Tumor and Choroidal Nevusmentioning
confidence: 99%
“…In 2005, Shields and associates analyzed 120 naevi and detected SRF in only 3% of these [10,11] . The author described other common OCT abnormalities overlying the tumour, which included retinal degeneration (42%), thinning (22%), oedema (15%) and pigment epithelial detachment (13%).…”
Section: Discussionmentioning
confidence: 99%
“…Topography of choroidal naevi J Krohn et al in the posterior fundus, 1,16,17 as well as having a predilection for both the nasal 9 and temporal quadrants. 4,8,15 In our study, the naevi were uniformly concentrated in the posterior pole.…”
Section: Discussionmentioning
confidence: 99%